2018
DOI: 10.1007/s00213-018-5099-x
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and alcohol: a multifaceted relationship

Abstract: Background: Arginine vasopressin (VP) has been implicated in a number of neuropsychiatric disorders with an emphasis on situations were stress increased the severity of the disorder. Based on this hypothesized role for VP in neuropsychiatric disorders, much research is currently being undertaken in humans and animals to test VP as a target for treatment of a number of these disorders including alcohol abuse. Objectives: To provide a summary of the literature regarding the role of VP in alcohol and stress rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 167 publications
(240 reference statements)
2
15
0
Order By: Relevance
“…The comprehensive and accurate characterization of transcriptional activity represents an important step in the understanding of chronic alcohol exposure in which gene expression occurs in the hypothalamic neurons. Many studies, including ours, have found that chronic alcohol drinking resulted in persistent changes in cytoplasmic mRNA levels of opioid and stress genes in rodent hypothalamus . In the present study, we hypothesized that alcohol‐induced transcriptional regulation in the nucleus is the critical step for maintaining the persistent changes in cytoplasmic mRNA levels and then subsequent peptide activity that is critically involved in excessive alcohol drinking.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The comprehensive and accurate characterization of transcriptional activity represents an important step in the understanding of chronic alcohol exposure in which gene expression occurs in the hypothalamic neurons. Many studies, including ours, have found that chronic alcohol drinking resulted in persistent changes in cytoplasmic mRNA levels of opioid and stress genes in rodent hypothalamus . In the present study, we hypothesized that alcohol‐induced transcriptional regulation in the nucleus is the critical step for maintaining the persistent changes in cytoplasmic mRNA levels and then subsequent peptide activity that is critically involved in excessive alcohol drinking.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies, including ours, have found that chronic alcohol drinking resulted in persistent changes in cytoplasmic mRNA levels of opioid and stress genes in rodent hypothalamus. 11,15,19 In the present study, we hypothesized that alcohol-induced transcriptional regulation in the nucleus is the critical step for maintaining the persistent changes in cytoplasmic mRNA levels and then subsequent peptide activity that is critically involved in excessive alcohol drinking. Therefore, we investigated the effects of chronic alcohol and acute withdrawal on opioid and stress gene expressions at nuclear transcriptional activity in the hypothalamus.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Alcohol abuse is believed to contribute to the onset of over 60 types of diseases and injuries and a cause of at least 200 others at the same time [6]. Excessive alcohol consumption leads to the severe failures of digestive, cardiovascular, and nervous (central and peripheral) systems [6][7][8][9][10]. The most frequent disorders related to alcohol abuse include alcoholic liver disease (including steatosis, steatohepatitis, cirrhosis, or hepatocellular carcinoma), pancreatitis, gastritis, hypertension, arrhythmia, or cardiomyopathy [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%